"What Is This, the Seventies?" Spectres of the Past (and the Future) in Recent Northern Irish Television. (May 2022) - Coulter, Colin
For all the gains made during its celebrated peace process, Northern Ireland remains haunted by a conflict that claimed more than 3, 700 lives. One of the spaces in which the ghosts of the past manifest themselves is that of television drama. In this article, Mark Fisher's reading of "hauntology" provides the theoretical frame for an analysis of two recent TV series set in Northern Ireland: The Fall and Derry Girls . Although the programs could not be more different in both tone and content, they both illustrate sharply that the region remains, in John Hewitt's indelible phrase, a "ghost-haunted land." In particular, The Fall and Derry Girls reveal that Northern Ireland continues to be deeply troubled both by those who were lost during the conflict and by that which was lost in the transition to peace.